Privacy and occupational health services. Issue 9 (30th August 2006) - Heikkinen, A; Launis, V; Wainwright, P; Leino-Kilpi, H
Abstract : Privacy is a key ethical principle in occupational health services. Its importance is emphasised in several laws, in ethical codes of conduct as well as in the literature, yet there is only very limited empirical research on privacy in the occupational health context. Conceptual questions on privacy in the occupational health context are discussed. The baseline assumption is that, in this context, privacy cannot be approached and examined only from the employee's (an individual) vantage point but the employer's (a group) point of view must also be taken into account, and that the concept has several dimensions (physical, social, informational and psychological). Even though privacy is a basic human need, there is no universally accepted definition of the concept and no consensus on whether an organisation can have privacy in the same way as people do. Many of the challenges surrounding privacy in the context of occupational health seem to be associated with the dual loyalties of occupational health professionals towards the employee and employer and with their simultaneous duties of disseminating and protecting information (informational privacy). Privacy is thus not an absolute value, but more research is needed to understand its multidimensional nature in the context of occupational health.